No safe secret - Michaels, Fern (Kensington Publishing Corp., 2016)
From her silver Mercedes to her designer kitchen, Molly's life is gleaming and beautiful, at least on the surface. Married to Tanner, a top cosmetic dentist, she has a wonderful daughter finishing high school and twin stepsons from Tanner's first marriage. No one in her exclusive neighborhood in Goldenhills, Massachusetts, knows what living with the demanding Tanner is really like. They know even less about the life she left behind in Florida almost two decades ago.